The Inferno of Pinocchio: Dante’s Legacy in Le avventure di Pinocchio by Carlo Collodi - Gussago, Luigi; Pagani, Andrea (Spunti e Ricerche, 2022)
This article investigates textual and theme-related connections between Collodi’s Le avventure di Pinocchio and Dante’s Divina commedia, with Inferno as the main focus. In late-nineteenth-century Italy the figure of Dante faced a substantial revival after almost two hundred years of neglect. With their literary and political efforts, intellectuals like De Sanctis or Cantù proclaimed Dante one of the Padri of the recently constituted Italian nation. The famous Statue of Dante in Piazza Santa Croce in Florence, for instance, was inaugurated in 1865 to celebrate the author. Starting from the most recent interpretations of Pinocchio as an anti-establishment text, this article investigates correlations with Dante’s poem. In light of this, we propose to read the puppet’s conversion into a middleclass prototype as the climax of a journey that shares some key aspects with Dante’s descent to the underworld. The comparative analysis of the two works also underlines significant echoes of the Commedia in Pinocchio with regard to character representations, references to place, or the use of imagery. For example, in the final scene of Pinocchio the wooden puppet becomes a mere physical vessel, an empty shell separated from the soul: an epilogue that evokes one of the theological foundations of the Inferno.